Sulfonium salt compound, photoacid generator, and resist composition

By designing a sulfonium salt compound with a specific structure and controlling the acid diffusion length in the photoresist, the problem of photoresist difficulty in forming high-resolution patterns is solved and higher-quality photolithography patterns are achieved.

CN119330865APending Publication Date: 2025-01-21HUBEI DINGLONG CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310901539.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

With the finerization of photolithography technology, the diffusion length of the photoacid generator in the photoresist is getting closer and closer to the pattern size formed, making it difficult to form a high-resolution pattern, and the higher the resolution, the mask error factor and The more obvious the line width roughness problem is.

Method used

Using a sulfonium salt compound, its structure is specifically designed to generate acid when illuminated, control the acid diffusion length, and improve the solubility and dispersion of the acid through the design of the anionic part, thereby reducing the mask error factor and improving the lithography pattern line width regularity.

Benefits of technology

It effectively reduces the mask error factor, improves the line width regularity and resolution of the lithography pattern, and forms a higher quality lithography pattern.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004351897610000051
    Figure BDA0004351897610000051
  • Figure BDA0004351897610000054
    Figure BDA0004351897610000054
  • Figure BDA0004351897610000055
    Figure BDA0004351897610000055
Patent Text Reader

Abstract

The embodiment of the invention provides a sulfonium salt compound, a photoacid generator and a resist composition, and relates to the field of photoresist. The sulfonium salt compound disclosed by the embodiment of the invention has a specific structural general formula, and the sulfonium salt compound with the structural general formula can be completely soluble and uniformly dispersed in an organic solvent, so that the uniformity of the composition can be ensured when the sulfonium salt compound is used as the resist composition; when the sulfonium salt compound provided by the embodiment of the invention is used as a photoacid generator for the resist composition, a large steric hindrance group of the sulfonium salt compound can effectively reduce MEEF and improve the LWR performance of a photoetching pattern; and ester groups in the sulfonium salt compound enable the sulfonium salt compound to be easily decomposed, so that the influence on the environment can be reduced to the greatest extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photoresists, and in particular to a sulfonium salt compound, a photoacid generator, and an anti-etching agent composition. Background Art

[0002] When preparing highly integrated semiconductor chips, photolithography is generally used to etch the wafer. Photolithography refers to the technology of transferring the pattern on the mask to the substrate with the help of photoresist (also known as photoresist) under the action of light. The main process is: first, light passes through the mask to irradiate the surface of the wafer with a layer of photoresist film, causing a chemical reaction in the photoresist in the exposed area; then, the photoresist in the exposed area or the unexposed area is dissolved and removed by developing technology (the former is called positive photoresist and the latter is called negative photoresist), so that the pattern on the mask is copied to the photoresist film; finally, the pattern on the mask is finally transferred to the substrate using etching technology. As the integration level of semiconductor chips becomes higher and higher, the wavelength of exposure light needs to be shorter and shorter in order to form high-resolution patterns and thus make high-performance chips. The current mainstream practice is to use light waves with a wavelength of 193nm and below for lithography (generally referred to as ArF lithography technology). In ArF lithography technology, light waves are also allowed to pass through media such as water to further improve the resolution of the pattern through refraction. This is generally called immersion lithography.

[0003] The components of photoresist generally include base resin, photo acid generator (PAG), etc. The photo acid generator is a photosensitive compound that can decompose and produce acid under light. These acids will act as catalysts to promote the reaction of the base resin during the baking process after exposure to make the base resin more soluble or insoluble in the developer, thereby producing a prefabricated pattern.

[0004] However, as photolithography technology continues to become increasingly miniaturized, the diffusion length of the photoacid generator in the photoresist is getting closer and closer to the size of the pattern formed, making it increasingly difficult to form a high-resolution pattern on the photoresist. In addition, the higher the resolution, the larger the mask error enhance factor (MEEF) of the photoresist, causing a sharp deviation in line width, and the line width roughness (LWR) of the pattern is also greatly affected by the acid diffusion. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a sulfonium salt compound, a photoacid generator, and a resist composition, which can reduce MEEF and improve the LWR performance of the resist composition, thereby preparing a highly integrated chip with better resolution.

[0006] In the first aspect, the embodiments of the present application provide a sulfonium salt compound, the general structural formula of which is: Wherein, R1 and R2 are independently C1~C 20 Aliphatic hydrocarbon group, C1~C 20 Any one of aliphatic hydrocarbon groups; R3 to R5 are each independently at least one of hydrogen, alkyl, alkoxy, and fluorine-containing groups; R f1 ~R f4 Each is independently fluorine or a fluorinated alkyl group; n is any integer between 1 and 4.

[0007] In the above technical solution, the sulfonium salt compound can generate acid when exposed to light, and the generated acid can denature the polymer compound such as the matrix resin, thereby changing the solubility of the polymer compound itself; after the matrix resin coated with the sulfonium salt compound is developed, a specific pattern can be generated on the polymer compound such as the matrix resin. In addition, the inventors have found that in the sulfonium salt compound that meets the above structural formula, since the anion part has a long alkyl chain, and the alkyl chain also binds the sterically hindered norbornene group to R f1 ~R f4 The anion part of the sulfonium salt compound is completely soluble and uniformly dispersed in the organic solvent; since the anion part of the sulfonium salt compound of the above structural formula contains a sterically hindered norbornene group and a lactone group, and the two are directly connected by a covalent bond, the combination of the two can effectively control the length of acid diffusion, and combined with R f1 ~R f4 The fluorine-containing groups in the sulfonium salt compound (fluorine-containing groups can enhance the acidity of the sulfonium salt compound after light exposure) can effectively reduce MEEF and improve the LWR performance of the photolithographic pattern. In addition, the inventors have also found that the lactone group can not only effectively control the length of acid diffusion, but also is easy to degrade, so that after use, the sulfonium salt compound can be degraded to minimize its impact on the environment.

[0008] Furthermore, in the above-mentioned sulfonium salt compound, R3 to R5 in the cationic part are selected from at least one of hydrogen, alkyl, alkoxy, and fluorine-containing groups, which is beneficial for the sulfonium salt compound to maintain a balance between solubility and photosensitivity.

[0009] In one possible implementation, R f1 ~R f4 are each independently fluoro or trifluoromethyl; optionally, R f1 ~R f4 At least two of them are fluorine.

[0010] In the above technical solution, the fluorine atom or trifluoromethyl group can enable the sulfonium salt compound to better control the acid diffusion length; and the fluorine atom substituent is easier to synthesize and has higher acidity than other fluorine-containing groups such as trifluoromethyl.

[0011] In a possible implementation, C1~C 20 The aliphatic hydrocarbon group includes at least one of a branched aliphatic hydrocarbon group and a cyclic aliphatic hydrocarbon group; 20 The aliphatic hydrocarbon group includes at least one of an adamantyl group and a tert-butyl group.

[0012] In the above technical scheme, the steric hindrance of cyclic aliphatic groups and branched aliphatic groups is greater than that of straight-chain aliphatic groups, so the acid diffusion length of the sulfonium salt compound can be reduced; for example, adamantyl, tert-butyl, etc., have greater steric hindrance than straight-chain aliphatic groups with the same number of carbon atoms.

[0013] In a second aspect, an embodiment of the present application provides a photoacid generator, the components of which include the above-mentioned sulfonium salt compound.

[0014] In the above technical solution, the photoacid generator containing the above sulfonium salt compound can effectively control the acid diffusion length when irradiated with light, thereby reducing the MEEF during photolithography and improving the LWR performance of the photolithographic pattern.

[0015] In a third aspect, an embodiment of the present application provides an anti-corrosion agent composition, the components of which include the photoacid generator of the second aspect, a base resin, a quencher, and a solvent; the base resin is a polyacrylate derivative, the quencher is an ionic organic substance, and the acidity of the quencher is lower than the acidity of the photoacid generator.

[0016] In the above technical solution, the matrix resin of the polyacrylate derivative can allow light with a wavelength of 193nm and below to pass through, thereby ensuring that other components in the composition can be irradiated by light; the photoacid generator can generate acid under light irradiation, thereby causing the matrix resin to be denatured, thereby changing the solubility of the matrix resin. In addition, the acid diffusion length of the above-mentioned photoacid generator is small, so that the LWR performance of the photolithographic pattern on the resist composition can be improved, thereby forming a pattern with higher resolution.

[0017] In addition, in the resist composition, the quencher can capture the excess acid compounds generated by PAG to prevent other regions of the matrix resin from being denatured; therefore, the quencher is generally selected to be an ionic organic substance with weaker acidity. The solvent can dissolve the remaining components to ensure that the composition is relatively uniform.

[0018] In one possible implementation, the repeating unit of the matrix resin is Where R Ais at least one of hydrogen, methyl, and trifluoromethyl; L G is an acid-labile group; Y is a polar group having at least one structure selected from cyano, carbonyl, carboxyl, ether bond, ester bond, sulfonate bond, carbonate bond, lactone ring, sultone ring, and carboxylic anhydride.

[0019] In the above technical solution, L G Groups such as Y can react with acids, thereby changing the solubility of the matrix resin, so that a pre-designed lithography pattern can be photoetched on the matrix resin.

[0020] In one possible implementation, L G The group is at least one of the following:

[0021] And / or, the Y group is at least one of the following:

[0022] In a possible implementation, the weight average molecular weight of the matrix resin is 1000 to 10000; optionally, the weight average molecular weight of the matrix resin is 1000 to 7000; and / or the dispersion degree of the matrix resin is 1.0 to 2.0.

[0023] In the above technical solution, the matrix resin satisfying the above weight average molecular weight has good etching resistance and also avoids any resolution reduction problem caused by the inability to establish a dissolution rate difference before and after exposure; a narrower dispersion is conducive to forming a more precise lithography pattern on the matrix resin.

[0024] In one possible implementation, the cation of the quencher is at least one of the following:

[0025] And / or, the anion of the quencher is at least one of the following:

[0026] In a possible implementation, the components of the resist composition further include a surfactant, the surfactant is a fluorine-containing resin, and the surfactant has a repeating unit shown in the following general structural formula: Wherein R is any one of hydrogen, fluorine, methyl, and trifluoromethyl; L G is an acid-labile group; R f5 It is a fluorinated hydrocarbon having 1 to 30 carbon atoms.

[0027] In the above technical scheme, the surfactant needs to be a fluorine-containing resin, so that after the resist composition is spin-coated into a film, the surfactant just has a tendency to separate on the resist surface, so as to achieve the effect of minimizing water penetration or leaching. Due to the existence of the surfactant, water and water-soluble components are not easy to ooze out from the resist film formed by the resist composition, so the resist composition containing the surfactant can play a good role in protecting the exposure copolymerization. In addition, due to containing specific acid dissociative groups in the surfactant, its solubility in the alkaline development after exposure and PEB (Post Exposure Bake, baking after exposure) can increase, thereby can be removed. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present application embodiment clearer, the technical scheme in the present application embodiment will be clearly and completely described below. If the specific conditions are not specified in the embodiment, it is carried out according to the conditions recommended by normal conditions or manufacturers. If the reagents or instruments are not specified by the manufacturer, they are all conventional products that can be obtained by commercial purchase. In addition, if not otherwise specified, the "parts" in the present application embodiment represent the mass fractions.

[0029] The sulfonium salt compound, photoacid generator, and resist composition of the embodiments of the present application are described in detail below.

[0030] The general structural formula of the sulfonium salt compound of the embodiment of the present application is as follows:

[0031]

[0032] In the above structural formula, R1 and R2 are independently C1 to C 20 Aliphatic hydrocarbon group, C1~C 20 Any one of aliphatic hydrocarbon groups; R3 to R5 are each independently at least one of hydrogen, alkyl, alkoxy, and fluorine-containing groups; R f1 ~R f4 Each is independently fluorine or a fluorinated alkyl group; n is any integer between 1 and 4.

[0033] The sulfonium salt compound in the embodiment of the present application is an ionic organic substance, which can generate acid under light, and the generated acid can easily denature high molecular organic substances such as polyacrylic acid resin, thereby changing the solubility of such high molecular organic substances. According to this principle, a predetermined pattern can be formed on the polyacrylic acid resin by adding a sulfonium salt compound to the polyacrylic acid resin, and finally the pattern can be transferred to the semiconductor material by using etching technology, thereby completing the etching of semiconductor materials such as wafers to form chips.

[0034] The applicant found that in the embodiments of the present application, when the norbornene group and the lactone group in the anion part are connected together and used in combination, the length of acid diffusion can be effectively controlled; these two groups are combined with R f1 ~R f4 Fluorinated groups such as ester groups can effectively reduce MEEF and improve the LWR performance of photolithographic patterns. In addition, the ester group is easy to decompose, so that the impact of sulfonium salt compounds on the environment can be minimized after use. As for the R1 and R2 groups in the ester group, they generally play a role in assisting the regulation of ester steric hindrance, which can be C1~C 20 Any aliphatic hydrocarbon group, C1~C 20 The aliphatic hydrocarbon group may be a straight chain structure or a branched chain or a cyclic structure, and examples thereof include methyl, isopropyl, sec-butyl, tert-butyl, tert-pentyl, n-pentyl, n-hexyl, n-octyl, n-nonyl, cyclopentyl, cyclohexyl, 2-ethylhexyl, cyclopentylmethyl, cyclopentylethyl, cyclopentylbutyl, cyclohexylmethyl, cyclohexylethyl, cyclohexylbutyl, norbornyl, adamantyl, adamantylmethyl and other alkyl groups, phenyl, naphthyl, anthracenyl and other aromatic groups, and the like. Moreover, since the steric hindrance of the branched chain or cyclic structure is large, it is beneficial to better control the acid diffusion length, so at least one of the branched chain aliphatic hydrocarbon group and the cyclic aliphatic hydrocarbon group is preferred; more specifically, it may be an aliphatic hydrocarbon group such as adamantyl and tert-butyl. In addition, C1~C 20 Some hydrogen atoms in the aliphatic hydrocarbon group may also be replaced by groups containing heteroatoms such as oxygen atoms, sulfur atoms, nitrogen atoms, halogen atoms, etc., or groups containing heteroatoms such as oxygen atoms, sulfur atoms, nitrogen atoms, etc. may exist between carbon atoms to form C1~C 20 Aliphatic hydrocarbon group, containing heteroatoms C1~C 20 The aliphatic hydrocarbon group may contain a hydroxyl group, a cyano group, a carbonyl group, an ether bond, a thioether bond, an ester bond, a sulfonate bond, a carbonate bond, a carbamate bond, a lactone ring, and the like.

[0035] Fluorinated groups can provide acidity to compounds after exposure to light, and they also play an important role when used in conjunction with large steric hindrance groups. Fluorinated groups such as fluorine atoms or trifluoromethyl groups can enable sulfonium salt compounds to better control the acid diffusion length. Therefore, R f1 ~R f4 The fluorine-containing groups are each independently fluorine or trifluoromethyl; further, R f1 ~R f4 At least two of them can be fluorine, which makes it easier to synthesize the target product. For ease of understanding, this embodiment gives the general structural formula of the anion part at this time:

[0036]

[0037] Due to the presence of large steric hindrance groups, their solubility is generally poor, the stacking degree is high, and it is difficult to completely dissolve and evenly disperse in organic solvents. Therefore, in the embodiment of the present application, the sterically hindered norbornene groups and ester groups are separated by long hydrocarbon chains and R f1 ~R f4 The anion of the sulfonium salt compound can be completely soluble and uniformly dispersed in an organic solvent. As an example, in this embodiment, n is generally 1, which can also reduce the difficulty of synthesis.

[0038] For ease of understanding, as an example, this embodiment shows that when n is 1, R f1 ~R f4 When at least two of them are fluorine, the specific structural formula of the anion structure of the partial sulfonium salt compound is as follows:

[0039]

[0040] In the sulfonium salt compounds of the embodiments of the present application, R3 to R5 of the cationic part are independently at least one of hydrogen, alkyl, alkoxy, and fluorine-containing groups, which also ensures that the cationic part can maintain a balance between solubility and photosensitivity.

[0041] For ease of understanding, this example also provides the specific structural formula of some cationic structures, as shown below:

[0042]

[0043] Of course, the present application also provides a specific preparation method of the above-mentioned sulfonium salt compound, and its synthesis route is as follows:

[0044]

[0045] If one wants to obtain sulfonium salt compounds with different substituents or different carbon chain lengths, one only needs to change the substituents and carbon chain lengths based on the raw materials. Therefore, this application will not describe in detail the synthesis method of each sulfonium salt compound.

[0046] The embodiment of the present application also provides a photoacid generator, the components of which include the above-mentioned sulfonium salt compound. The photoacid generator can effectively control the acid diffusion length when illuminated, thereby reducing the MEEF during photolithography and improving the LWR performance of the photolithographic pattern.

[0047] The embodiment of the present application also provides a resist composition, the components of which include the above-mentioned photoacid generator, base resin, quencher, and solvent.

[0048] <Matrix resin>

[0049] In the embodiment of the present application, the base resin is a polyacrylate derivative, and the base resin of the polyacrylate derivative can allow light with a wavelength of 193nm and below to pass through, thereby ensuring that other components in the composition can be irradiated by light; the photoacid generator can generate acid under light, thereby denaturing the base resin and changing the solubility of the base resin. Its repeating unit is generally Where R A is at least one of hydrogen, methyl, and trifluoromethyl; L G is an acid-labile group; Y is a polar group having at least one structure selected from cyano, carbonyl, carboxyl, ether, ester, sulfonate, carbonate, lactone, sultone, and carboxylic anhydride. G Groups such as Y can react with acids, thereby changing the solubility of the matrix resin, so that a pre-designed lithography pattern can be photoetched on the matrix resin.

[0050] Specifically, L G The group can be at least one of the following:

[0051] And / or, the Y group is at least one of the following:

[0052] The matrix resin is generally formed by polymerization of acrylate derivatives. For example, when L G When the group satisfies the above structural formula, the synthetic monomer corresponding to its repeating unit is generally:

[0053]

[0054] Similarly, when the Y group satisfies the above structural formula, the synthetic monomer corresponding to its repeating unit is generally:

[0055]

[0056] In addition, the weight average molecular weight (Mw) of the matrix resin is generally controlled in the range of 1000 to 10000; more specifically, Mw is generally 1000 to 7000. In this way, the matrix resin has sufficient etching resistance and avoids any resolution reduction problem caused by the inability to establish a difference in dissolution rate before and after exposure. Mw can be measured by gel permeation chromatography (GPC) using tetrahydrofuran (THF) solvent relative to polystyrene standards. Specifically, a GPC column manufactured by Agilent can be used, and the flow rate is 1.0 mL / min, tetrahydrofuran is used as the elution solvent, and the column temperature is 40°C. The analysis conditions are measured by gel permeation chromatography (GPC) with monodisperse polystyrene as the standard.

[0057] In addition, as the pattern rules become finer and finer, the influence of molecular weight and dispersity becomes stronger and stronger. Therefore, in order to formulate a resist composition suitable for high-resolution pattern formation, the polymer should preferably have a narrow dispersity of 1.0 to 2.0 (dispersity is expressed by Mw / Mn, Mn is the number average molecular weight). If the polymer has a broad molecular weight distribution or dispersity, which indicates that there are polymer parts with lower and higher molecular weights, there is a possibility that foreign matter is left on the pattern or the pattern profile is degraded. When the polymer contains the above two repeating units, the molar fraction of each unit preferably falls within the following range (mol%), but is not limited thereto: (I) 10-60 mol%, more preferably 20-50 mol%, further preferably 30-50 mol% of at least one repeating unit having formula (a), (II) 40-90 mol%, more preferably 50-80 mol%, further preferably 50-70 mol% of at least one repeating unit having formula (b). Wherein the formula (a) unit is a repeating unit with L G The repeating unit of formula (b) is a unit having a Y group.

[0058] <Quencher>

[0059] The quencher is also an ionic organic compound, and the acidity of the quencher is lower than that of the photoacid generator. In this way, the quencher can capture the excess acid compounds generated by the PAG to prevent other areas of the matrix resin that are not exposed to light from being denatured.

[0060] Specifically, the cation of the quencher is generally at least one of the structures shown below:

[0061]

[0062] As for the anion of the quencher, generally at least one of the following structural formulas can be selected:

[0063]

[0064] The above-mentioned cations and anions can be combined in pairs to form a complete quencher.

[0065] <Organic Solvents>

[0066] In the resist composition, the organic solvent can dissolve other components and ensure that the components of the resist composition are uniform, so that a photolithographic pattern with higher resolution can be formed when applied. As long as the organic solvent can dissolve other components, there is no specific restriction. For example, the organic solvent can be a ketone solvent such as cyclohexanone, methyl-2-n-pentyl ketone; an alcohol solvent such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol; an ether solvent such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether; an ester solvent such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate; a lactone solvent such as γ-butyrolactone; or any one or more mixed solvents. Among these organic solvents, in order to ensure good solubility, propylene glycol monomethyl ether acetate, cyclohexanone, γ-butyrolactone, and their mixed solvents are generally preferred.

[0067] <Surfactant>

[0068] In the resist composition of the present application embodiment, a surfactant may also be contained. The surfactant needs to be a fluorine-containing resin, so that after the resist composition is spin-coated into a film, the surfactant has a tendency to separate on the resist surface, so as to achieve the effect of minimizing water penetration or leaching. Due to the presence of the surfactant, water and water-soluble components are not easy to seep out from the resist film formed by the resist composition, so the resist composition containing the surfactant can play a good role in protecting the exposure copolymerization. In addition, the surfactant also needs to contain a specific acid dissociative group, so that its solubility in the alkaline development after exposure and PEB can increase, thereby being removed.

[0069] Specifically, the repeating unit of the surfactant is as follows:

[0070] Wherein R is any one of hydrogen, fluorine, methyl, and trifluoromethyl; L G is an acid-labile group, and the details can be referred to the foregoing content of this application; R f5 It is a fluorinated hydrocarbon having 1 to 30 carbon atoms, specifically, it can be F3C-*, Groups like these.

[0071] When a photolithography pattern is formed using the resist composition in the embodiment of the present application, the following steps are generally performed:

[0072] S100, film formation: coating a resist composition on a substrate and curing the resist composition to form a photoresist film.

[0073] In this step, the resist composition is generally coated on the substrate by a spin coater, and then the resist composition is cured by drying to form a photoresist film.

[0074] S200, immersion exposure: light of a specific wavelength is transmitted through a liquid medium and then irradiated onto a specific area of ​​the photoresist film for exposure.

[0075] In this step, light is generally passed through a mask so that the light is irradiated on a specific area of ​​the photoresist film; the liquid medium is generally water. The light first passes through the mask, then through the liquid medium, and then irradiates the surface of the photoresist film for exposure.

[0076] S300, development: treating the photoresist film with an alkaline aqueous solution.

[0077] In this step, the photoresist film in the exposed area can be removed by using an alkaline aqueous solution, thereby forming a high-resolution pattern on the surface of the photoresist film.

[0078] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0079] Example 1

[0080] This embodiment provides a sulfonium salt compound PAG1, and its specific synthesis route is as follows:

[0081] (1) Synthesis of Intermediate A: Cyclopentadiene (72.6 g, 1.1 mol) and adamantane acrylate (206 g, 1 mmol) were added to 500 mL of toluene, and after being stirred and dissolved uniformly, the mixture was heated to 60° C. and stirred under a nitrogen atmosphere for 4 hours until the adamantane acrylate was completely reacted. The solvent and excess cyclopentadiene were removed under reduced pressure to obtain 231 g of crude product, namely Intermediate A, which can be directly used in the next step. The yield of this step is 85%, and the chemical reaction formula is as follows:

[0082]

[0083] (2) Synthesis of intermediate B: Intermediate A (136 g, 0.5 mol) was dissolved in dichloromethane (400 mL), stirred and dissolved, and then hydrogen peroxide solution (30 wt% aqueous solution, 80 g) was added dropwise under ice-water bath cooling. The addition was completed within 30 minutes, and then the temperature was slowly restored to room temperature. The reaction was continued at room temperature for 4 hours. After the reaction was completed, sodium sulfite aqueous solution was added to the reaction system, and then the separated liquid was washed with water 3 times, and the organic layer solution was combined, and then anhydrous sodium sulfate was added to dry the organic layer solution, and the solvent was removed under reduced pressure to obtain 125 g of crude product of intermediate B, which was directly used in the next step. The chemical reaction formula of this step is as follows:

[0084]

[0085] (3) Synthesis of intermediate C: B (72 g, 0.25 mol) was dissolved in dichloromethane (200 mL), and a dichloromethane solution of adamantane carboxylic acid (45 g, 0.25 mol of adamantane carboxylic acid dissolved in 200 mL of dichloromethane) was added dropwise at room temperature, and the addition was completed within 30 minutes. After the addition was completed, the reaction was continued at room temperature for 4 hours. Sodium bicarbonate aqueous solution was added thereto, the organic layer was collected and then the water layer was extracted with dichloromethane, the organic layer solution was combined and dried with anhydrous sodium sulfate, and the solvent was removed under reduced pressure to obtain 94 g of intermediate C, which was directly used in the next step reaction. The yield of this step was 80%, and the chemical reaction formula was as follows:

[0086]

[0087] (4) Synthesis of Intermediate D: Carbonyldiimidazole (CDI, 16.2 g, 0.1 mmol) was added to a 500 mL tetrahydrofuran solution of 4-bromo-3,3,4,4-tetrafluorobutyric acid (26.8 g, 0.1 mol), and the mixture was stirred at room temperature for 2 hours. The mixture was then heated to 70°C, and Intermediate C (46.8 g, 0.1 mmol) was added to the reaction, and the reaction was carried out at 70°C for 16 hours under nitrogen protection.

[0088] After the reaction was completed, the solvent was removed under reduced pressure, and the residual oil was dissolved in 200 mL of dichloromethane. The dichloromethane was then washed with 200 mL of NH4Cl, twice in total, and then washed once with 200 mL of water. After washing, the dichloromethane solution was dried with MgSO4, and dichloromethane was removed under reduced pressure to obtain 52 g of intermediate D. The specific reaction formula is as follows:

[0089]

[0090] (5) Synthesis of Intermediate E: Intermediate D (28 g, 40 mmol) was dissolved in 200 mL of acetonitrile, and sodium dithionite (15.7 g, 90 mmol) and sodium bicarbonate (10 g, 120 mmol) were dissolved in 200 mL of deionized water. The stirred acetonitrile solution was added to the aqueous solution to form a mixture, and the mixture was stirred at 70° C. for 16 hours. 19 F-NMR detects whether the reaction is complete. After the reaction is complete, 100mL of water, 50mg of Na2WO4·2H20, and 14.5g of H2O2 (30wt% aqueous solution) are added to the reaction system, and the reaction is stirred at room temperature for 16 hours. After the reaction is completed, the organic phase is evaporated on a rotary evaporator, and the residual solid is dissolved in 100L of acetone, and then the solution is slowly poured into 2L of methyl tert-butyl ether. The waxy product is separated by decantation to remove the solvent, and the obtained waxy product is further dried under reduced pressure to obtain 19.7g of the crude product of intermediate E, which is directly used in the next step. The yield of this step is 68%, and the reaction formula is as follows:

[0091]

[0092] (6) Synthesis of PAG1: Add intermediate E (18 g, 25 mmol) and triphenylsulfonium bromide (TPSBr, 8.6 g, 54.5 mmol) to a mixture of 200 mL of dichloromethane and 200 mL of deionized water. Stir the reaction at room temperature overnight. After the reaction is completed, separate the aqueous phase and the organic phase, and wash the organic phase 5 times with 200 L of deionized water. Concentrate the separated organic phase and pour it into methyl tert-butyl ether to generate 22.5 g of the photoacid generator PAG1, with a yield of 93%. The reaction formula is as follows:

[0093]

[0094] The purity of the PAG1 sample was checked by HPLC-MS. The cation purity was 99.7% by UV at 220 nm and 99.4% by positive ion mass spectrometry. The anion purity was 99.8% by negative ion chromatography mass spectrometry (LCMS).

[0095] PAG1 in D6-DMSO 1 H-NMR data are as follows: δ (ppm): 7.33-7.36 (15H, m); 5.10-5.15 (2H, m); 2.62-2.67 (2H, m); 1.76-2.35 (39H, m).

[0096] LCMS: cation 263; anion 703.

[0097] Embodiments 2 to 4

[0098] According to the above-mentioned synthesis method, Examples 2 to 4 respectively provide a sulfonium salt compound, named PAG2 to PAG4, with the specific structures as follows:

[0099]

[0100] Application Examples

[0101] The present application provides a resist composition with different components to explore the effect of a photoacid generator on the performance of the resist composition. The components of the resist composition of the present application are specifically described as follows:

[0102] A represents a photoacid generator, and A1 to A7 correspond to PAG1 to PAG7, respectively.

[0103] The specific structural formulas of PAG5 to PAG7 are as follows:

[0104]

[0105]

[0106] B represents a quencher, and B1 is triphenylsulfonium salicylate, and B2 is triphenylsulfonium camphorsulfonate.

[0107] C represents an organic solvent, C1 represents propylene glycol monomethyl ether acetate, C2 represents γ-butyrolactone, and C3 represents cyclohexanone.

[0108] D represents the base resin, and its repeating unit is: Weight average molecular weight Mw = 6200, Mw / Mn = 1.42; 13 The results of C-NMR analysis showed that the molar ratio of a to b was 42:58.

[0109] E represents a surfactant, and its repeating unit is: Weight average molecular weight Mw = 5900, Mw / Mn = 1.5; 13 The results of C-NMR analysis showed that the molar ratio of c to d was 62:38.

[0110] In the resist composition, the composition containing A1 to A4 photoacid generators is used as an application example, and the composition containing A5 to A7 photoacid generators is used as a comparative example. The performance of different resist compositions is tested. The specific components of various resist compositions are shown in the following table:

[0111] Table 1 Components of different resist compositions

[0112]

[0113] For the resist compositions of Application Examples 1 to 7 and Comparative Examples 1 to 5, performance tests were performed on sensitivity, MEEF, and LWR according to the following evaluation methods.

[0114] A base antireflection film-forming composition (trade name: "ARC66") was applied to the surface of a 12-inch silicon wafer using a spin coater ("CLEANTRACK ACT12" manufactured by Tokyo Electron Co., Ltd.) to form a base antireflection film having an average thickness of 105 nm.

[0115] The resist compositions in all application examples and all comparative examples were respectively coated on the surface of a 12-inch silicon wafer using a spin coater, and then baked at 205°C for 60 seconds. After that, it was cooled at 23°C for 30 seconds to form a resist film with an average thickness of 85nm. Next, an ArF excimer laser immersion exposure system (model "TWINSCANXT-1900i", "produced by ASML Co.) was used under optical conditions to expose through a mask pattern with a line of 40nm and a spacing of 80nm. The exposure parameters were: NA of 1.35, annular (o-0.8 / 0.6). After exposure, PEB was performed at 95°C for 60 seconds. After that, an aqueous solution of tetramethylammonium hydroxide (TMAH) with a mass fraction of 2.38% was used to perform alkaline development on the resist film. After development, it was washed with water and then dried to form a positive resist pattern.

[0116] (1) Sensitivity test

[0117] The exposure dose when a 40 nm line and an 80 nm exposure pattern are formed on the resist composition after the ArF exposure is defined as the optimal exposure dose (i.e., the optimal E op ), and the best E op Used as sensitivity E op (Unit: millijoules / square centimeter, mJ / cm 2 ).

[0118] (2) MEEF test

[0119] Adopt the best E op , using mask patterns with target line widths of 40nm, 42nm, 44nm, 46nm, 48nm, and 50nm, respectively, LS patterns with a pitch of 90nm are formed. At this time, the slope of the straight line when the target size (nm) is plotted as the horizontal axis and the line width (nm) formed on the resist film using each mask pattern as the vertical axis is calculated as the MEEF performance. When the slope of the straight line is closer to 1, it means that the MEEF is better.

[0120] (3) LWR test

[0121] The line width of a 1:1 line-space pattern at 40 nm was measured under a SEM (scanning electron microscope) to determine the line width variation (30 points were measured and the 3σ value was calculated), which was recorded as LWR. The smaller the LWR value, the smaller the fluctuation of the line pattern and the better the profile.

[0122] The above measurement results are shown in the following table:

[0123] Table 2 Performance test results of application examples and comparative examples

[0124]

[0125] As can be seen from Table 2, the resist composition of the present invention is particularly suitable for ArF immersion lithography because it contains the sulfonium salt PAG, because it forms a pattern with high resolution, low LWR and low MEEF.

[0126] The above are only embodiments of the present application and are not intended to limit the scope of protection of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.

Claims

1. A sulfonium salt compound, characterized in that: Its general structure is shown below: Wherein, R1 and R2 are independently C1~C 20 Aliphatic hydrocarbon group, C1~C 20 Any one of aliphatic hydrocarbon groups; R3 to R5 are each independently at least one of hydrogen, alkyl, alkoxy, and fluorine-containing groups; R f1 ~R f4 Each is independently fluorine or a fluorinated alkyl group; n is any integer between 1 and 4.

2. The sulfonium salt compound according to claim 1, characterized in that R f1 ~R f4 are each independently fluoro or trifluoromethyl; optionally, R f1 ~R f4 At least two of them are fluorine.

3. The sulfonium salt compound according to claim 1 or 2, characterized in that C1~C 20 The aliphatic hydrocarbon group includes at least one of a branched aliphatic hydrocarbon group and a cyclic aliphatic hydrocarbon group; 20 The aliphatic hydrocarbon group includes at least one of an adamantyl group and a tert-butyl group.

4. A photoacid generator, characterized in that: Its components include the sulfonium salt compound described in any one of claims 1 to 3.

5. A resist composition, characterized in that Its components include base resin, quencher, solvent, and the photoacid generator described in claim 4; the base resin is a polyacrylate derivative, the quencher is an ionic organic matter, and the acidity of the quencher is lower than that of the photoacid generator.

6. The resist composition according to claim 5, characterized in that The repeating unit of the base resin is Where R A is at least one of hydrogen, methyl, and trifluoromethyl; L G is an acid-labile group; Y is a polar group having at least one structure selected from cyano, carbonyl, carboxyl, ether, ester, sulfonate, carbonate, lactone, sultone, and carboxylic anhydride.

7. The resist composition according to claim 6, characterized in that L G The group is at least one of the following: And / or, the Y group is at least one of the following:

8. The resist composition according to any one of claims 5 to 7, characterized in that The weight average molecular weight of the base resin is 1000 to 10000; optionally, the weight average molecular weight of the base resin is 1000 to 7000; And / or, the dispersion degree of the base resin is 1.0 to 2.

0.

9. The resist composition according to claim 5, characterized in that The cation of the quencher is at least one of the following: And / or, the anion of the quencher is at least one of the following:

10. The resist composition according to claim 5, characterized in that Its components also include a surfactant, which is a fluorine-containing resin, and the surfactant has a repeating unit shown in the following general structural formula: Wherein R is any one of hydrogen, fluorine, methyl, and trifluoromethyl; L G is an acid-labile group; R f5 It is a fluorinated hydrocarbon having 1 to 30 carbon atoms.

Citation Information

Cited By

  • Preparation method of p-tert-butylphenyl sulfurized cyclopentane trifluorosulfonate

    CN121021465A